Annual Report and Accounts for the year ended 30th June, 1985 (The Southern African Institute of Mining and Metallurgy, 1985)
Council and Standing Committees-1984/85 President: J.D. Austin Vice Presidents: H.E. James and Dr H. Wagner Immediate Past President: Prof. R.P. King Honorary Treasurer: Prof. D.G. Krige Members of Council: B.C. Alberts, Prof. S. Budavari, E.B. Crocker, N.J. Devine, C.E. Fivaz, J.S. Freer, Prof. G.G. Garrett, J.J. Geldenhuys, Dr A.K. Haines, R.W.O. Kersten, Dr B.K. Loveday, I.D. Matthews, G. Maude, H.G. Mosenthal, B.E. Protheroe, Dr O.K.H. Steffen, Dr P.T. Wedepohl Chairman, Witbank/Middelburg Branch: W.C. Mather Chairman, Orange Free State/Klerksdorp Branch: Dr M.A. Orridge Past Presidents Serving on Council: Dr M.G. Atmore, Prof. A.N. Brown, Dr P.R. Jochens, G.Y. Nisbet, Prof. R.P. Plewman, Dr R.E. Robinson, Prof. M.D.G. Salamon, P.W.J. van Rensburg, D.A. Viljoen, P.A. von Wielligh Standing Committee Chairmen: Adjudication, Prof. R.P. King; Awards, Prof. R.P. King; Constitution, Rules and Policy, Prof. R.P. King; Excursions and Banquet, B.E. Protheroe; Journal, H.E. James; Membership, Dr H. Wagner; Phoenix National Committee, Dr M.G. Atmore; SAIMM School-Extractive Metallurgy, J.S. Freer; SAIMM School-Mining, Prof. S. Budavari; Special Publications, J.D. Austin; Technical Programme¬Extractive Metallurgy, Dr B.K. Loveday; Technical Programme-Mining, J.J. Geldenhuys; Technical Programme-Physical Metallurgy, Dr P.T. Wedepohl; Training, Career Guidance and Education, Prof. R.P. King; World Mining Congress-National Committee, Prof. R.P. Plewman; Working Group Physical Metallurgy, Prof. G. G. Garrett